The Relatives' Big Five Personality Influences the Trajectories of Recovery of Patients After Severe TBI: A Multilevel Analysis. Issue 4 (13th May 2016) - Haller, Chiara S.
Abstract: This study examines the influence of the personality of relatives on the trajectories of recovery of patients with severe traumatic brain injury (TBI). The present subsample ( N = 376) of a larger population‐based, prospective, 12‐month multicenter cohort study in Switzerland (2007–2011) consists of patients with severe TBI (age ≥ 16) and their relatives. The predictors are the NEO Five‐Factor Inventory and time (trajectory of functioning of the patient over time). The outcomes are the patients' (a) neurological functioning; (b) reported emotional, interpersonal, cognitive, and total functioning post‐injury; and (c) health‐related quality of life (HRQoL). The covariates included Abbreviated Injury Scale score of the head region and age. Results for patients > 50 are (a) relatives' Extraversion influenced patients' total, interpersonal, and cognitive functioning; (b) relatives' Agreeableness influenced patients' interpersonal functioning; and (c) relatives' Conscientiousness influenced patients' physical HRQoL ( p s < .05). Results for patients ≤ 50 are (a) relatives' Neuroticism influenced patients' neurological and emotional functioning, and (b) relatives' Extraversion influenced patients' emotional functioning and psychological HRQoL ( p s < .05). The personality traits of the relative covary with the functioning of the patient, and psychological adaptation to the loss of function may progress at a later stage after physical health improvements have been achieved. Thus, a biopsychosocial perspective on the rehabilitation process is needed.